Health and Welfare on Youth Development Index in Special Region of Yogyakarta - Admiwati, Rini; Sugiyanto, Sugiyanto (Asian Journal of Healthcare Analytics, 2025)
This study aims to see the contribution of the health and welfare domain in realizing the Youth Development Index in the Special Region of Yogyakarta. The method used in this study is a qualitative method with a type of literature study research. The data sources used are secondary data sources consisting of reference books, journals, articles, and related documents tracked from the Yogyakarta Education, Youth, and Sports Office and the internet. Data validation or data validity test in this study uses source triangulation techniques. Source triangulation to test the credibility of a data is carried out by checking the data that has been obtained from various data sources. Data analysis uses qualitative analysis. The results of the study show that the low value of IPPs in the health and welfare domain in Yogyakarta is caused by the lack of health education, limited access to mental health services, permissive social norms for risky behavior, and peer influence are the main challenges and also limited resources in implementing policies, especially in suburban areas. Evaluation of government policies and programs such as health campaigns, training, and socialization programs has not been fully effective, especially in changing social norms and behaviors among adolescents.